2023
DOI: 10.1108/jtf-09-2022-0221
|View full text |Cite
|
Sign up to set email alerts
|

Exploring governance effectiveness, tourism development and poverty reduction relationship in SAARC countries using panel dynamic estimation

Abstract: PurposeThe present study aims to examine the moderating impact of governance quality on the tourism poverty nexus using a panel of six South Asian Association for Regional Cooperation (SAARC) countries during the period 2002 to 2019.Design/methodology/approachFor the soundness of the results, fully modified ordinary least square (FMOLS) and dynamic ordinary least square (DOLS) econometric models were applied to determine the long-run relationship.FindingsThe findings confirmed the positive and significant impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In the same line, Shah (2023) found that governance quality positively and significantly affect poverty reduction in a panel of six SAARC countries between 2002 and 2019. Similarly, Jindra and Vaz (2019) used a multilevel Probit model to investigate the nexus between governance quality and poverty reduction in 71 countries from 2009-2014.…”
Section: Empirical Literaturementioning
confidence: 76%
“…In the same line, Shah (2023) found that governance quality positively and significantly affect poverty reduction in a panel of six SAARC countries between 2002 and 2019. Similarly, Jindra and Vaz (2019) used a multilevel Probit model to investigate the nexus between governance quality and poverty reduction in 71 countries from 2009-2014.…”
Section: Empirical Literaturementioning
confidence: 76%